Case Report: A Clinical and Genetic Analysis of Childhood Growth Hormone Deficiency With Familial Hypercholesterolemia - Yang, Shengmin; Ke, Xiaoan; Liang, Hanting; Li, Ran; Zhu, Huijuan (Frontiers in Endocrinology, 2021)
Background: Growth hormone deficiency (GHD) is a developmental disorder in children characterized by low growth hormone (GH), short stature and unfavorable lipid profiles. Familial hypercholesteremia (FH) is an inborn disorder of low-density lipoprotein cholesterol (LDL-C) metabolism which results in premature cardiovascular events. The co-occurrence of GHD and FH, which may aggravate the hypercholesteremic condition in the affected individuals, had rarely been discussed in previous publication. Methods: This work reports two cases of GHD with FH, and explores the lipid profiles of GHD children and their therapeutic response to recombinant human growth hormone (rhGH). The diagnosis of GHD is based on low peak GH level ( <7 ng/mL) in GH provocation test. FH is diagnosed by high LDL-C level (≥ 4 mmol/L) and confirmed genetic mutations in the LDL-C metabolic pathway. We also searched all previously published metabolic studies on GHD children as of December 31, 2020. Information on their LDL-C, duration and dose of rhGH treatment were retrieved and summarized. Results: The first case was a 5.3 year-old boy. His height was 103.6 cm (SDS = -2.29) and his peak GH in provocative test was 6.37 ng/mL. Additionally, his LDL-C was 4.80 mmol/L and he harbored a heterozygous mutation for the apolipoprotein B (APOB) gene (c.10579 C > T). The second case was a 9-year-old girl at the height of 117.3 cm (SDS = -2.91). Her GH peaked at 4.99 ng/mL in insulin-induced hypoglycemic test and 2.80 ng/mL in L-dopa test. Her LDL-C was 6.16 mmol/L, and she carried a mutated copy of the low-density lipoprotein receptor (LDLR) gene (c.809 G > A). Literature review indicated that GHD children suffered from higher baseline LDL-C, but it was significantly reduced after rhGH treatment. Conclusions: FH should be considered if a GHD child has remarkably elevated LDL-C that cannot be attributed to low GH level alone. Genetic mutations in the LDL-C metabolic pathway prevent the body from effectively metabolizing lipids, thereby resulting in early-onset hypercholesteremia and probably playing a negative role in children’s growth.